2020
DOI: 10.1002/apj.2600
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐free extraction of resveratrol and its glycoside from Japanese knotweed rhizome by liquefied dimethyl ether without pretreatments

Abstract: Herein, we carried out the extraction of polyphenol resveratrol and its glycoside (piceid) from raw Japanese knotweed via a simple method, employing dimethyl ether (DME) as the solvent. With DME extraction, the conventional drying and cell wall disruption steps can be left out. As a result, more resveratrol and piceid were obtained in DME extraction than in conventional ethanol extraction. Because the Hansen solubility parameters of DME are closer to ethanol than to water, it allowed us to extract resveratrol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Absolute stilbene content amounted to 155.078 mg/100 g fluid extract ( Table 4 ) and could easily be improved through scale-up processes like large batch processing and concentration of constituents by evaporation of solvent. A stilbene extraction from fresh R. japonica rhizome with liquified dimethyl ether was reported to yield 0.342 mg/g resveratrol and 2.57 mg/g polydatin, calculated per gram of dry rhizome [ 25 ]. Extraction of resveratrol from dried and pulverized R. japonica rhizome with deep eutectic solvents (DES) yielded up to 9.00 mg/g dry rhizome [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absolute stilbene content amounted to 155.078 mg/100 g fluid extract ( Table 4 ) and could easily be improved through scale-up processes like large batch processing and concentration of constituents by evaporation of solvent. A stilbene extraction from fresh R. japonica rhizome with liquified dimethyl ether was reported to yield 0.342 mg/g resveratrol and 2.57 mg/g polydatin, calculated per gram of dry rhizome [ 25 ]. Extraction of resveratrol from dried and pulverized R. japonica rhizome with deep eutectic solvents (DES) yielded up to 9.00 mg/g dry rhizome [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have shown that liquefied DME can extract a variety of functional substances, such as astaxanthin [50,51], fucoxanthin [52], lutein [29,53], resveratrol and its glycosides [54], catechins and caffeine [55], tocopherol [56], gingerols and capsaicin [27]. Among these substances, carotenoids, such as astaxanthin, fucoxanthin and lutein, are hydrophobic, therefore difficult to encapsulate into liposomes by mechanical methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the HPS concept, the intermolecular interactions are classified into three components: δd (the energy from dispersion forces between molecules), δp (the energy from dipolar intermolecular forces between molecules), and δh (the energy from hydrogen bonds, π-π stacking interactions, coordination bonds, and charge transfer interactions), which are used to estimate the ease of mutual solubility. The δd, δp, and δh values for DME are 15.2 MPa 1/2 , 6.1 MPa 1/2 , and 5.7 MPa 1/2 [39], and those for CO 2 are 15.7 MPa 1/2 , 6.3 MPa 1/2 , and 5.7 MPa 1/2 [40]. The similarity of the properties of the extracts by SC-CO 2 extraction and SC-CO 2 with DME extraction is supported by the HPS concept that solutes are readily soluble in solvents that have similar three-dimensional vectors of HPS parameters [41].…”
Section: Properties Of the Extracts And Residuementioning
confidence: 97%